An Axial-Vector Photon in a Mirror World (Contemporary Mathematics, 2024)
We discuss a theory in which the left- and right-handed axial-vector photons refer to long- and short-lived bosons of true neutrality, respectively. Such a difference in lifetimes expresses the unidenticality of masses, energies, and momenta of axial-vector photons of the different components, generalizing the classical Klein-Gordon equation to the case of C-odd types of particles with a nonzero spin. Together with a new Dirac equation for truly neutral particles with the half-integral spin, the latter admits the existence of the second type of the local axial-vector gauge transformation responsible for origination in a Lagrangian of an interaction Newton component, which gives an axial-vector mass to all the interacting particles and fields. The quantum axial-vector mass, energy, and momentum operators constitute herewith a new Schrödinger equation, confirming that each of them can individually influence on the matter field. They define at the new level, namely, at the level of the mass-charge structure of gauge invariance another Euler-Lagrange equation such that it has an axial-vector nature.
Keywords: mass energy and momentum matrices; a set-matrix duality; C-odd particles with a nonzero spin; mass energy and momentum operators; gauge transformations of the second type; an interaction newton component; selected quantum theory equations